Role of the Transcriptional Corepressor Bcor in Embryonic Stem Cell Differentiation and Early Embryonic Development - Wamstad, Joseph Alan (Public Library of Science, 2008)
Bcor (BCL6 corepressor) is a widely expressed gene that is mutated in patients with X-linked Oculofaciocardiodental (OFCD) syndrome. BCOR regulates gene expression in association with a complex of proteins capable of epigenetic modification of chromatin. These include Polycomb group (PcG) proteins, Skp-Cullin-F-box (SCF) ubiquitin ligase components and a Jumonji C (Jmjc) domain containing histone demethylase. To model OFCD in mice and dissect the role of Bcor in development we have characterized two loss of function Bcor alleles. We find that Bcor loss of function results in a strong parent-of-origin effect, most likely indicating a requirement for Bcor in extraembryonic development. Using Bcor loss of function embryonic stem (ES) cells and in vitro differentiation assays, we demonstrate that Bcor plays a role in the regulation of gene expression very early in the differentiation of ES cells into ectoderm, mesoderm and downstream hematopoietic lineages. Normal expression of affected genes (Oct3/4, Nanog, Fgf5, Bmp4, Brachyury and Flk1) is restored upon re-expression of Bcor. Consistent with these ES cell results, chimeric animals generated with the same loss of function Bcor alleles show a low contribution to B and T cells and erythrocytes and have kinked and shortened tails, consistent with reduced Brachyury expression. Together these results suggest that Bcor plays a role in differentiation of multiple tissue lineages during early embryonic development.